PENGEMBANGAN AGRIBISNIS CABAI MERAH (Capsicum annuum L) DI KABUPATEN MAGELANG - Ernoiz Antriyandarti; Susi Wuri Ani (Trunojoyo University of Madura, 2015)
One of major commodity of horticulture in Central Java Province is chili (Capsicum annuum L). As a central area for agribusiness of Chili, Magelang needs the development to stimulate investment growth potential by involving all regional agribusiness, government, farmers/ agribusiness and private groups to work together in an integrated. This study aims to (1) Determine the feasibility of chilli farm; (2) Knowing the comparative advantage of the chili farm; and (3) Formulate developing agribusiness of Chili.This research uses descriptive analytical method. On farm analysis, quantitative data are converted and tabulated in the same unit. To determine the feasibility of Chili farm used analysis of R/C ratio. The greater the value of R/C ratio was more viable farm. Determination of comparative advantage of Chili is analyzed by the Policy Analysis Matrix (PAM). PAM results show the individual and collective effects of price and factor policies. Furthermore, this method can analyze the comparative advantage of a commodity.The result showed that Agribusiness of Chili is profitable both the private and social, and there are no disadvantage caused by the activities of Chili agribusiness. Thus agribusiness of chili can be further developed. The nontradeable inputs of chili farming have been used efficiently and provide added value for farmers. Domestic demand of chili is more profitable supplied by domestic production rather than imports. Farmers receive chili prices lower than it should and not get product price protection. Farmers pay the nontradeable input lower than it should. As for the tradeable inputs, farmers pay higher than it should. It can be concluded that the chili agribusiness has not received adequate protection.